2001
DOI: 10.1002/pola.1130.abs
|View full text |Cite
|
Sign up to set email alerts
|

The tenth anniversary of Suzuki polycondensation (SPC)

Abstract: This article describes the successful transfer of the Suzuki cross-coupling (SCC) reaction to polymer synthesis, one of the major developments within the last decade of polymer synthesis. The polymers prepared by Suzuki polycondensation (SPC) and its Ni-catalyzed reductive counterpart are soluble and processable poly(arylene)s that, because of their rigid and conjugated backbones, are of interest for the materials sciences. Achievable molar masses easily compete with those of traditional polyesters and polyami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 66 publications
1
36
0
Order By: Relevance
“…In the course of our studies we found that the use of free hydroxy groups in Suzuki-cross-coupling reactions leads to the formation of undesirable side products. [24] For that reason the OH-group of the 2-bromofluorene 6 was protected with tetrahydropyran (THP). [25] After the Suzuki-cross-coupling the THP group is cleaved quantitatively with a small amount of HCl.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…In the course of our studies we found that the use of free hydroxy groups in Suzuki-cross-coupling reactions leads to the formation of undesirable side products. [24] For that reason the OH-group of the 2-bromofluorene 6 was protected with tetrahydropyran (THP). [25] After the Suzuki-cross-coupling the THP group is cleaved quantitatively with a small amount of HCl.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[243] The prospects of the Suzuki coupling was reviewed by Schlüter on occasion of its 10 th anniversary. [244] The formation of polyarylenes proceeds via the repeated sequences of oxidative addition of aryl halides, boronic acids, or triflates on palladium(0) and formation of palladium(II) biaryl complexes followed by reductive elimination, carbon-carbon crosscoupling, and recovery of palladium(0). The catalytic cycle of polyarylenevinylene formation involves the repeated reaction sequences of oxidative addition followed olefin insertion, b-hydride elimination, and HX abstraction in the presence of a base to regain palladium(0).…”
Section: Heck Stille and Suzuki Coupling Reactionsmentioning
confidence: 99%
“…The polymer syntheses are carried out using either Stille [29] or Suzuki [30] coupling reaction (Scheme 2). The BT copolymers P2ICTT and P3ICTT are synthesized using 5,5 0 -ditrimethylstannyl-2,2 0 -bithiophene [31,32] and compounds 3 or 4 in THF with a catalytic amount of Pd(PPh 3 ) 4 .…”
Section: Synthesis Of Monomers and Polymersmentioning
confidence: 99%
“…Moreover, thiophene units should have some good impact over the molecular organization as found with copolymers based on fluorene and indenofluorene. [28] For all these reasons, we report the synthesis of 2,8-and 3,9-poly(indolocarbazole-alt-bithiophene)s using either Stille [29] or Suzuki [30] coupling. Moderate electrondonating unit, bithiophene (BT), and strong electrondonating unit, bis(3,4-ethylenedioxythiophene) (BiEDOT), have been incorporated to the polymeric structures.…”
Section: Introductionmentioning
confidence: 99%